Сучасні тенденції та перспективи розвитку бутік-готелів - Пенчук, Владислав Миколайович; Цирульнікова, Віта Валентинівна; Тищенко (Усатюк), Олена Михайлівна; Бортнічук, Олег Вікторович (My University, 2018)
У статті розглядається основні особливості та концепція бутік-готелів. Досліджено європейський досвід та перспективи розвитку готелів формату «бутік» на сучасному вітчизняному ринку готельного господарства, перспективи використання інноваційних засобів залучення та утримання гостей. Визначено сегмент ринку, на який розраховані послуги та переваги у використанні сучасних дизайнерських рішень в інтер`єрі номерного фонду. In the article the concept of boutique hotels is considered, the main features of this type of hotel enterprises are investigated, current trends and prospects of development of boutique hotels segment in the world hotel market are analyzed. Prospects of Hotels format " boutique " on the national market modern hotel industry, analysis of European and Ukrainian experience of the hotel, prospects of innovative means of attracting and retaining customers. Deals with competitiveness and unique boutique hotels. Defined market segment, which services and benefits designed to use modern designs in interior room stock.
Keywords: бутік-готелі; готельний продукт; досвід подорожі; boutique hotels; hotel product; travel experience; кафедра готельно-ресторанної справи